Coaching performance and leadership behaviours in team sports - König, S. (Sportwissenschaft, 2013)
The aim of this study was to investigate coaching performance in team sports taking leadership behaviours into focus. To do so, coaching performance was put in a literature-based frame and analysed with reference to a task structure based on the idea of hierarchical planning. The focus of the paper is on a mixed methods multi-strand study using qualitative as well as quantitative threads to develop and verify a set of coaching strategies focussing on teambuilding and team leadership. Qualitative analyses showed that coaches do have a clear understanding of forming and leading a team, which could be shown by a specific set of strategies being used by high performance coaches from different team sports (basketball, football, handball, and volleyball). These strategies could be confirmed in a sequential quantitative study analysing coaches` and players` attitudes towards the previously analysed schemes. The results of this study are discussed in terms of methodical and practical implications.